Selection strategy of second-line biologic therapies in adult patients with ulcerative colitis following prior biologic treatment failure: Systematic review and meta-analysis - Hu Zhang; Chenlu Mu; Yu Gu; Fanyi Meng; Xiali Qin; Hailong Cao (Pharmacological Research, 2024)
Background: Optimizing second-line biologic therapies for adult ulcerative colitis (UC) post first-line failure is essential. Objective: Compare second-line biologic therapy efficacy in adult UC patients with prior treatment failure. Methods: A comprehensive search of electronic databases up to May 2023 was conducted to assess second-line biologic therapy efficacy using a random effects model. Parameters analyzed included clinical remission rate, clinical response rate, mucosal healing rate, annual discontinuation rate, and colectomy rates. Results: Forty-three research papers were analyzed. Clinical remission rates for second-line biologics were ranked at 6–14 weeks: Infliximab (30%) was followed by Vedolizumab (29%), Ustekinumab (27%), and Adalimumab (19%). At 52–54 weeks, the order shifted, with Vedolizumab (35%) followed by Infliximab (32%), Ustekinumab (31%), and Adalimumab (26%). The mucosal healing rate was 21%, ranked as: Infliximab (31%), Vedolizumab (21%), Adalimumab (21%), and Ustekinumab (14%). The annual discontinuation rate stood at 20%, with Adalimumab (25%), Vedolizumab (18%), Infliximab (17%), and Ustekinumab (16%). Discontinuation rates due to primary failure (PF), secondary failure (SF), and adverse events (AE) were 6%, 12%, and 3%, respectively. The annual colectomy rate was 9%, with Adalimumab (15%) followed by Vedolizumab (10%), Ustekinumab (9%), and Infliximab (5%), and colectomy rates of 10% due to PF, 12% due to SF, and 4% due to AE. Conclusion: For UC patients with first-line treatment failure, it is recommended to prioritize infliximab or vedolizumab as second-line biologic therapies, while avoiding adalimumab as the primary choice. Further clinical trials are necessary to assess ustekinumab efficacy accurately.